(untitled) - Bhaskar, S. M. (Oxford, U.K., 2008)
As governments, IT companies and citizens become more dependent on information systems, the need to understand and devise information security systems has become very important. This title takes a practical approach to information security with emphasis on developing skills required for facing modern security related challenges. The book s organization is based on a common body of knowledge for security domain. Although this book is focused on practical issues, the fundamental principles have not been ignored. The book will be useful for IT professionals, students of M.Sc. (Computer Science), M.Sc. (IT), and faculty of Computer Science and Engineering Departments of various institutes and universities.
Keywords: Computer security,Computer networks; Security measures